Periodicity of Operation and Shrimp Catch from Different Harvesting Methods in Traditional Farms at Vypeen Island - P., Pravin; K., Ravindran (Fishery Technology, 2025)
Harvesting of shrimps in filtration farms is being done periodically through sluice gate and other fishing methods like gill net, cast net, drag net and hand picking. Six seasonal and six perennial prawn filtration farms were selected for studying the periodicity of operation and shrimp catch from different harvesting methods employed in traditional filtration shrimp farms at Vypeen island. The average catch from all the gears operated in the seasonal farm was 408.1 kg.ha"1 and 384 kg.ha"1 during 1999-2000 and 2000-2001 respectively and the average catch from all the gears operated in perennial farm was 268.2 kg.ha"1 during 1999-2000. Catch of shrimps in sluice net dominated in both the seasonal and perennial farms contributing 94 % and 71 % respectively, followed by gillnet, cast net and handpicking. The gear wise catch from seasonal and perennial farms is discussed